Review of the Palearctic Atemelia Herrich-Schäffer (Lepidoptera, Yponomeutoidea, Praydidae), with description of a new leafmining species - Liu, Tengteng; Yan, Jiahe (Zootaxa, 2017)
The Palearctic Atemelia Herrich-Schäffer, 1853 is reviewed. Two species are treated, one of which is described as new: A. fusca Liu, sp. nov. The genus Atemelia is recorded in China for the first time, and it is also newly recorded from the Eastern Palearctic region. Larvae of A. fusca sp. nov. mine leaves of Ulmus pumila (Ulmaceae), sharing the same host plant genus with another leaf miner A. torquatella (Lienig & Zeller, 1846) from Europe, but they are distinctive from the Nearctic and the Neotropical Atemelia species in host plant families and life styles. Photographs of adults and genitalia of the Palearctic Atemelia are provided. Additional photographs of immature stages, leafmines, and host plant are provided for the new species. In addition, three DNA barcodes are provided for A. fusca sp. nov.